A Narrative Review of the Pathophysiology and Treatment of Hypertrophic Cardiomyopathy. Issue 12 (December 2022) - Gelpi Acevedo, Lee M.; Salinas, Alexandra Lizette; Polanco, Juan Sebastian; Nizami, Hamasah; Marsh, Denise; Patel, Meet; Parikh, Kinna; Jain, Rahul; Jain, Rohit
Abstract : Hypertrophic cardiomyopathy (HCM) is an autosomal dominant disorder that is caused by mutations in β-myosin heavy chain and myosin-binding protein C. In young athletes, HCM is the most common cause of sudden cardiac death. This article provides a brief overview on risk factors, genetic implications, clinical presentation, and management of HCM. Abstract: Hypertrophic cardiomyopathy (HCM) is a genetic autosomal dominant disorder of the heart muscle that is characterized by left ventricular hypertrophy and sudden cardiac death. It is the most common inherited cardiac disease. HCM is defined by sarcomeric mutations that result in fibrosis of the heart, affecting contraction. In most cases, clinical presentations can range from asymptomatic to systolic and diastolic ventricular dysfunction, arrhythmias, and sudden cardiac death. Some histopathologic features typical of the disease are changes in myocyte disarray and myocardial fibrosis. Mutations in the β-myosin heavy chain and myosin-binding protein C have been identified as the cause of the disease. The goals of pharmacological therapy as well as nonpharmacological therapy are to alleviate the symptoms and to prevent sudden cardiac death. Anatomical defects are treated primarily by surgical intervention, whereas other issues such as hypercontractility are treated with pharmacotherapy. In this article, we review the pathophysiology and treatment options for HCM.